Salience bias and overwork - Fabio Römeis; Fabian Herweg; Daniel Müller (Games, 2022)
In this study, we enrich a standard principal-agent model with hidden action by introducing salience-biased perception on the agent's side. The agent's misguided focus on salient payoffs, which leads the agent's and the principal's probability assessments to diverge, has two effects: First, the agent focuses too much on obtaining a bonus, which facilitates incentive provision. Second, the principal may exploit the diverging probability assessments to relax participation. We show that salience bias can reverse the nature of the inefficiency arising from moral hazard; i.e., the principal does not necessarily provide insufficient incentives that result in inefficiently low effort but instead may well provide excessive incentives that result in inefficiently high effort.
Keywords: 330; context-dependent preferences; hidden action; moral hazard; overwork; salience theory